Legu Gam Sebagai Refleksi Relasi Antaretnik Pada Kemajemukan Masyarakat Ternate - Hudan Irsyadi (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2015)
This research is about cultural study that focuses on the relationship amongethnic on pluralism of Ternate societies through the Legu gam festival. Legugam for Ternate community is public party. The changing concept of legudance to be legu gam as the festival of Ternate society is the political cultureafter the conflict to raise the togetherness and also to show the symbolicpower of the sultan of Ternate. The power is placed on the importance ofbalakusu se kano-kano (culture society), which generally represent thepluralism of Ternate community who symbolically united in legu gam.In this case, festival legu gam is the negotiation and a diverse representationof ethnic identity. Theory of Bourdieu, habitus of, is used to see how thecapitals such as economic, social, cultural and symbol related among ethnicrelations in legu gam festival. These various capitals are then framed withinthe concept of interactive multiculturalism to understand how the diverseidentity is communicated culturally.The findings showed that the legu gam festival is diverse ethnic identities thatcome together as a representative on resources they have. In this context, theethnic identity negotiation occurs at the legu gam festival. So that it hasbecome an annual ritual that becomes multicultural interactions to facilitatecultural interests and the existence of each ethnic.